COMPARATIVE STUDIES OF PITUITARY GLAND EXTRACT, OVAPRIN HORMONE AND COST BENEFIT ON HATCHABILITY AND FRY QUALITIES OF CATFISH (CLARIAS GARIEPINUS) - Usman M.B.; Olukotun O.; Suleiman R.; Aasa O.S.; Apene E.; Obekpa N.B.; Rasheed F.M.; Afolabi A.O.; Okechalu S.O.; Asuquo J.N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
This study examined the Hatchability, growth performance and profitability of Clarias gariepinus hatched with Ovaprim and pituitary hormone using reproductive output and fry quality indices. Six pairs of broods stock (Cat fish) with three pairs, each for artificial and natural hormones were selected from both male and female and were subjected to different treatment with ova prim (Artificial hormone) and pituitary gland extract (natural hormones). At a mean temperature of 25.0±0.81 latency period for ova prim and pituitary gland extract were 650 and 698 minutes, respectively. Workers fecundity was significantly higher (P<0.05) for brooders treated with ova prim than pituitary hormone induced spawners. Hatching rates also followed the same trend, in which significantly higher hatching success was recorded for ova prim ovulated eggs (90.2%) than the pituitary hormone induced eggs (70.33%) fry survival rate was 91.7±1.20% for Ovaprim induced fish while pituitary hormone induced fish fry had 87.8±1.23%; percentage deformed fry was significantly minimal for Ovaprim treated fish. Production cost analysis revealed the use of pituitary produced a statistically significant gross profit and a higher profit index of 99.22 over the Ovaprim although Ovaprim was productive with a good yield for the cost amount. It was concluded from the study is that Ovaprim is superior hence it was recommended for use by catfish breeders while further research is been conducted on the use of pituitary hormone.